The evolution and genetics of thermal traits in Drosophila melanogaster - Fallis, Lindsey Caroline (Kansas State University, 2012)
Temperature is a critical environmental parameter and thermal variation has significant effects on local adaptation and species distributions in nature. This is especially true for organisms that are isothermal with their environment. Variation in temperature imposes stress and directly influences physiology, behavior, and fitness. Thus, to thrive across a range of thermal environments populations must contain sufficient genetic variation, the capacity to respond plastically, or some combination of both genetic and plastic responses. In this work I first quantified patterns of phenotypic and genetic variation in nature and then dissected the genetic basis of variation in thermal traits. In the first aim I used natural populations of Drosophila melanogaster collected from a latitudinal transect in Argentina to investigate variation in heat stress resistance and cold plasticity within and among populations. I found heat stress resistance was highly variable within populations, but was strongly associated with the monthly maximum average temperature of each site. For cold plasticity I was able to demonstrate significant variation in plasticity within and among populations, however the among population variation was best explained by the altitude of each site. I hypothesized that this was caused by a difference in temperature fluctuations at high altitude sites relative to low altitude sites. To evaluate this hypothesis I paired our study with existing laboratory data that demonstrated significant fitness differences between high and low plasticity (and altitude) sites when these populations were reared in variable thermal environments. Thus, cold plasticity is an adaptive response to environmental variation. The final project focused on understanding the genetic basis of thermal variation. I fine-mapped a single co-localized heat and cold tolerance QTL via deficiency and mutant complementation mapping to identify four novel thermal candidate genes. There was no overlap of the deficiencies or genes associated with cold or heat stress resistance. Sequence analysis of each gene identified the polymorphisms that differentiate the lines. To test for independent associations between these polymorphisms and variation in nature the Drosophila Genome Reference Panel was used to confirm associations between allelic variation and cold tolerance in nature.
Keywords: thermal traits; Drosophila; phenotypic plasticity; deficiency mapping; Biology (0306)